2017
DOI: 10.1002/pssa.201700059
|View full text |Cite
|
Sign up to set email alerts
|

Chemical bath deposition of well-aligned ZnO nanorod arrays on Ag rods for photoelectrocatalytic degradation of rhodamine B

Abstract: Phone: þ86 150 9328 3484, Fax: þ86 371 6776 6629ZnO nanorod arrays (NAs) were prepared by a simple two-step process on the Ag rods. The X-ray diffraction and HRTEM characterizations indicated that ZnO nanorods were hexagonal wurtzite single crystalline structure. Photoelectrocatalytic performances of Ag rods with ZnO NAs (ZnO NAs/Ag rods) were studied systematically for the removal of rhodamine B (RhB). Under the optimal condition, the photoelectrocatalytic efficiency was nearly twice the photocatalytic effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Morphologies, structures and components of materials XRD patterns and SEM of ZnO are shown in Figure S1 and Figure S2 (Supporting information). Similar to previous reports, [23] the diffraction peaks are indexed to the hexagonal wurtzite-structured ZnO (PDF#36-1451) and the samples are rod-like arrays with an average diameter of 60 nm approximately. [24] As shown in Figure 1a, XRD patterns of the as-prepared CsPbBr 3 /Cs 4 PbBr 6 show that all the observed diffraction peaks can be attributed to the diffraction of CsPbBr 3 (PDF#54-0751) and Cs 4 PbBr 6 (PDF#73-2478) respectively, indicating that the asprepared products are CsPbBr 3 /Cs 4 PbBr 6 composites.…”
Section: Resultssupporting
confidence: 80%
“…Morphologies, structures and components of materials XRD patterns and SEM of ZnO are shown in Figure S1 and Figure S2 (Supporting information). Similar to previous reports, [23] the diffraction peaks are indexed to the hexagonal wurtzite-structured ZnO (PDF#36-1451) and the samples are rod-like arrays with an average diameter of 60 nm approximately. [24] As shown in Figure 1a, XRD patterns of the as-prepared CsPbBr 3 /Cs 4 PbBr 6 show that all the observed diffraction peaks can be attributed to the diffraction of CsPbBr 3 (PDF#54-0751) and Cs 4 PbBr 6 (PDF#73-2478) respectively, indicating that the asprepared products are CsPbBr 3 /Cs 4 PbBr 6 composites.…”
Section: Resultssupporting
confidence: 80%
“…As mentioned in the introduction, Han et al 30 A control experiment was conducted by studying the degradation of this dye under UV-ABC irradiation in the absence of electrodes. In this case, about 39% removal of MB was obtained.…”
Section: 2investigation Of Pec Efficiency Of Zno Nanorodsmentioning
confidence: 99%
“…When the potential is applied a reduction of the recombination the photo-generated electron-hole pairs occurs and consequently an increase of the PC efficiency is obtained. 28,29 Nevertheless, at the best of our knowledge, only a few studies are found in the literature using ZnO nanostructures as a photoanode for PEC, including the studies of Hunge et al 6 , Han et al 30 , Liu et al 31 , Lin et al 32 , Suryavanshi et al 33 , and Sarwar et al 34 These employ nanostructured ZnO as photoanodes for PEC. In addition, only the work of Han et al 30 used ZnO synthesized by CBD as a photoanode for PEC applications.…”
Section: Introductionmentioning
confidence: 99%
“…For the treatment of industrial wastewater, the traditionally used technologies are mainly chemical, physicochemical, and biological methods, including electrocatalytic degradation, [1][2][3][4] ultrasonic treatment, 5,6 biological occulation, 7,8 adsorption, 9,10 and photocatalytic degradation. [11][12][13][14][15][16] Photocatalytic degradation, namely, photocatalytic oxidation technology, which uses sunlight and simulated natural light as light sources to act on semiconductor catalysts to produce photogenerated electrons and holes, and reacts with O 2 , H 2 O, and other active substances to generate hydroxyl radicals, superoxide radicals, and other active substances, and eventually decomposes pollutants into harmless inorganic small molecules.…”
Section: Introductionmentioning
confidence: 99%